Leishmaniosis in children Leishmaniosen im kindesalter - Bogdan, Christian (Monatsschrift Kinderheilkunde, 2006)
Leishmaniosis is a protozoan infection that is acquired by the bites of sandflies. It is prevalent on all continents including various vacation areas for German tourists (e.g. Mediterranean countries and islands). Depending on the parasite species and strain as well as on the host immune response, the infection leads to papules or ulcers (cutaneous leishmaniosis) or to fever, hepatosplenomegaly and pancytopenia (visceral leishmaniosis). Diagnosis is made by the detection of the pathogen (histology, PCR and culture) in specialised laboratories. Unlike cutaneous leishmaniosis which requires a specific therapy only under certain conditions, visceral leishmaniosis must be treated. The drug of choice is liposomal amphotericin B. Despite successful treatment, later reactivation of the disease can occur during immunosuppression. There is no commercial vaccine available. The only prophylaxis is protection against sandfly bites. © Springer Medizin Verlag 2006.
CRIS-Team Scopus Importer:2024-02-26
Keywords: Cutaneous leishmaniosis; Hepatosplenomegaly; Pancytopenia; Skin lesions; Visceral leishmaniosis